2013
DOI: 10.1590/1679-775720130201
|View full text |Cite
|
Sign up to set email alerts
|

Etidronate from Medicine to Endodontics: effects of different irrigation regimes on root dentin roughness

Abstract: An increase in dentin roughness, associated with surface composition, contributes to bacterial adherence in recontaminations. Surface roughness is also important for micromechanical interlocking of dental materials to dentin, and understanding the characteristics of the surface is essential to obtain the adhesion of root canal sealers that have different physico-chemical characteristics.ObjectivesTo evaluate the effects of sodium hypochlorite (NaOCl), ethylenediaminetetraacetic (EDTA), etidronic (HEBP), and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 30 publications
5
32
0
4
Order By: Relevance
“…These results are in accordance with those of Tartari et al, 30 who reported that despite differences in the structure of the roots thirds, the resulting alterations were found to be similar.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with those of Tartari et al, 30 who reported that despite differences in the structure of the roots thirds, the resulting alterations were found to be similar.…”
Section: Discussionsupporting
confidence: 93%
“…25,26 Here, in both iRoot SP and AH Plus groups, final irrigation with 9% etidronic acid resulted in slightly higher bond strength values than those achieved with 17% EDTA and 1% PAA irrigation. Despite some differences in the irrigation protocols, this finding is in agreement with a recent study, 27 which showed an improvement in the bond strength of AH Plus when a chelating irrigation protocol involving a mixture of 18% etidronic acid and 5% NaOCl was used in the instrumentation phase.…”
Section: Discussionmentioning
confidence: 88%
“…Associado ao preparo mecânico, a substância química irrigadora preconizada foi o hipoclorito de sódio a 2,5%. Esta solução é a mais comumente empregada por possuir excelentes atividades antimicrobianas e de dissolução tecidual 14 .…”
Section: Discussionunclassified